UJI KANDUNGAN PROTEIN PADA BEBERAPA VARIETAS UMBI UBI KAYU ( Manihot esculenta Crantz) YANG DIHASILKAN DI DESA RANDOTONDA, KECAMATAN ENDE, KABUPATEN ENDE - Martinus Laka; Emilia S.A. Wangge (Agriculture Faculty of Flores University, 2018)
This study aims to determine the protein content found in all three cassava varieties. The cassava varieties produced in Randotonda Village, namely the cassava variety, the variety of cassava Ai land, and the flour cassava varieties. Test the protein content of several cassava varieties with varied harvest ages using the Kjedhal method. Cassava varieties of Tanah ai varieties with an harvest age of 8 months, cassava tubers, 10 months old verietas, and cassava flour 12 months old.The results showed that the three types of fresh cassava tubers of White variety were 1.59%, Tanah Ai cassava varieties were 1.48% and Wheatwood sweet potato varieties were 1.18%. This is because the White yam variety is 8 months old, while the 10-month AI variety and the Wheat variety are 12 months (1Year).